THE ANALYSIS OF MAXIMS IN “HARRY POTTER AND THE DEATHLY HALLOW PART 1” MOVIE - Nernere, Regina Putri (LATTE: A Journal of Language, Culture, and Technology ISSN 3063-0754, 2024)
This study examines the application of Grice's maxims in the movie "Harry Potter and the Deathly Hallows Part 1," emphasizing their role in ensuring effective communication. Grice's Cooperative Principle suggests that conversations should follow four maxims: quality, quantity, relevance, and manner, to facilitate clear and meaningful exchanges. However, these maxims are not always followed, leading to misunderstandings and misinterpretations. This study identifies instances where characters either fulfil or violate these maxims and analyses the effects of these violations on the overall communication process. Employing a qualitative descriptive method, the research collects and examines dialogues from the movie to categorize instances of adherence and violation of Gricean maxims. The findings indicate that violations of maxims often occur for humorous, dramatic, or deceptive purposes, affecting the audience’s perception and interpretation of dialogues. Characters such as Dobby, Ron, and Kreacher frequently violate maxims of quantity, relevance, and quality, either by providing excessive information, deviating from the topic, or delivering untruthful statements. Conversely, characters like Mad-Eye Moody and Lupin exemplify the fulfilment of maxims, ensuring clarity and coherence in conversations. The study contributes to the understanding of pragmatics in cinematic dialogue and highlights how filmmakers use language strategically to shape character interactions. The findings suggest that the violation of conversational maxims in movies is an intentional linguistic tool that enhances storytelling and audience engagement.